2020
DOI: 10.5897/ajmcsr2019.0785
|View full text |Cite
|
Sign up to set email alerts
|

Volatility measure of Nigeria crude oil production as a tool to investigate production variability

Abstract: The interest to carry out volatility analysis of crude oil production in Nigeria in this paper is motivated by the shortfalls in quantities of crude oil produced in recent past, given the country's high dependence on oil and its contribution to the nation's economic development. In 2016 precisely, the country experienced drastic instability in prices of crude oil at international markets and dwindling production quantities due to vandalism on oil facilities and other corrupt practices in the sector. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This study indicated that despite the changes in the oil price, the energy consumption associated with oil is still the same or considerable due to low investment in other sources of energies. Usoro et al [20] fitted crude oil series variance with ARCH (2), ARCH (3) and GARCH (3,3) models and also fitted to the ARIMA (0, 1, 1) variance of the error. This study suggested that GARCH and ARCH captured the fluctuation in the series while bilinear non-linear component of the model parameter did not show evidence of volatility clustering.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated that despite the changes in the oil price, the energy consumption associated with oil is still the same or considerable due to low investment in other sources of energies. Usoro et al [20] fitted crude oil series variance with ARCH (2), ARCH (3) and GARCH (3,3) models and also fitted to the ARIMA (0, 1, 1) variance of the error. This study suggested that GARCH and ARCH captured the fluctuation in the series while bilinear non-linear component of the model parameter did not show evidence of volatility clustering.…”
Section: Introductionmentioning
confidence: 99%